Closing the gap : forty years of economic progress for Blacks - Smith, James P., 1943-; Welch, Finis, 1938-; Rand eBooks (Santa Monica, CA : RAND, 1986)
This report undertakes a reassessment of the economic progress of American blacks over the past 40 years, drawing on the 1980 Census micro data file and the newly released micro data files for the 1940 and 1950 Censuses. Its most basic concern is whether the economic lot of black men has improved significantly in the 40-year period, but it also considers whether economic progress has touched all parts of the black community. Finally, it attempts to isolate the underlying causes of black economic progress by considering the roles played by education, migration to the north, and affirmative action.
"February 1986."
Includes bibliographical references (p. 127-128).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: African Americans -- Economic conditions; Electronic books